Effect of Ta Content on Scratching Behavior of Ti-Al-Ta-N Coatings on Titanium Substrate - Artur Shugurov; Evgenii Kuzminov (Metals, 2022)
The effect of Ta alloying on the structure, mechanical properties and scratching behavior of Ti-Al-N-based coatings deposited on Ti substrates by reactive direct-current magnetron sputtering is studied. It was found that increasing the Ta content in the Ti1-x-yAlxTayN coatings from y = 0 to y = 0.65 led to a decrease in hardness and Young’s modulus but an increase in the hardness-to-modulus ratio. This resulted in the reduction of the load-bearing capacity of the Ta-alloyed coatings and enhancement of their toughness. The competition among these trends determined the improved crack resistance and adhesion of the Ti0.31Al0.34Ta0.35N coating under scratching.